-9=-5(8-2k)+3(k-7)

Simple and best practice solution for -9=-5(8-2k)+3(k-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=-5(8-2k)+3(k-7) equation:


Simplifying
-9 = -5(8 + -2k) + 3(k + -7)
-9 = (8 * -5 + -2k * -5) + 3(k + -7)
-9 = (-40 + 10k) + 3(k + -7)

Reorder the terms:
-9 = -40 + 10k + 3(-7 + k)
-9 = -40 + 10k + (-7 * 3 + k * 3)
-9 = -40 + 10k + (-21 + 3k)

Reorder the terms:
-9 = -40 + -21 + 10k + 3k

Combine like terms: -40 + -21 = -61
-9 = -61 + 10k + 3k

Combine like terms: 10k + 3k = 13k
-9 = -61 + 13k

Solving
-9 = -61 + 13k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-13k' to each side of the equation.
-9 + -13k = -61 + 13k + -13k

Combine like terms: 13k + -13k = 0
-9 + -13k = -61 + 0
-9 + -13k = -61

Add '9' to each side of the equation.
-9 + 9 + -13k = -61 + 9

Combine like terms: -9 + 9 = 0
0 + -13k = -61 + 9
-13k = -61 + 9

Combine like terms: -61 + 9 = -52
-13k = -52

Divide each side by '-13'.
k = 4

Simplifying
k = 4

See similar equations:

| 5x-20=10x+15 | | -5(3a+6)=-105 | | 9y=7y+24 | | 5+4t=7(t) | | -16x^2+60x=56 | | 4a+3(a-2)=2(3a-2) | | 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y | | 1000x+50=30 | | -1+m=m-8 | | -27y=-108 | | -6x^2+3=-15 | | 4y+2=180 | | -6f+1=13 |

Equations solver categories